Modelling and control of a Magneto-Rheological elastomer for impact reduction - Mohd Sabirin Rahmat; Khisbullah Hudha; Zulkiffli Abd Kadir; Nur Rashid Mat Nuri; Noor Hafizah Amer; Shohaimi Abdullah (Journal of Mechanical Engineering and Sciences, 2019)
This article presents the simulation analysis on the effectiveness of impact reduction control based magneto-rheological elastomer isolator device (MREID). The MREID is one of the impact isolator devices that produce controllable stiffness by controlling the input current supply to the device coil. In order to control the input current for MREID, a hybrid control structure combining the skyhook and active force control strategy (HYSAFC) is proposed. Firstly, the characteristics of MREID in squeeze mode are investigated systematically in order to establish the relationship between the supply input current to the subsequent force and impact energy within the MREID. The proposed control strategy is used for force tracking control in determining the amount of input current to be applied to the MREID. The desired input current is determined by a current generator that is developed using inverse ANFIS technique which will regulate the current amount based on the desired force and impact energy. The effectiveness of the actively controlled MREID is evaluated using MATLAB simulations by comparing the performance of the MREID controlled by skyhook control against a passive damper. It is shows that the proposed controller recorded better response compared to skyhook controller, thus improving the stability and the effectiveness in controlling the MRE isolator device.